Microbial food webs in hypertrophic fishponds: Omnivorous ciliate taxa are major protistan bacterivores. (29th July 2019) - Šimek, Karel; Grujčić, Vesna; Nedoma, Jiří; Jezberová, Jitka; Šorf, Michal; Matoušů, Anna; Pechar, Libor; Posch, Thomas; Bruni, Estelle P.; Vrba, Jaroslav
Abstract: Despite the importance of shallow lakes worldwide, knowledge of microbial components, the base of their food webs, remains scarce. To close this gap, we investigated planktonic microbial food webs, in particular protistan bacterivory (for both ciliates and heterotrophic nanoflagellates [HNF]), in 10 shallow hypertrophic fishponds in South Bohemia (Czech Republic). We used fluorescently labeled bacteria as bacterivory tracers to estimate how abundant protistan populations in fishponds (4–25 × 10 3 HNF mL −1 and 55–770 ciliates mL −1 ) contribute to total bacterial mortality. Fluorescence microscopy, innovative image processing tools, and quantitative protargol staining were combined to detect major bacterivorous and omnivorous ciliate taxa. We quantified bacterial production, bacterivory by individual ciliate species, total ciliates, and total protistan bacterivory in all fishponds. On average, ciliate bacterivory was comparable to that of HNF, accounting for 56% and 44% of total protistan grazing, respectively. We found that primarily bacterivorous Peritrichia (genera Vorticella, Epistylis ) and Scuticociliata ( Cyclidium spp.) contributed only moderately (mean 26%) to total ciliate bacterivory. Unexpectedly, but highly abundant omnivorous Halteria/Pelagohalteria (Stichotrichia) and, to a lesser extent, also omnivorous Rimostrombidium spp. (Oligotrichia) contributed significantly more (mean 71%) to total ciliate bacterivory than typical bacterivorous taxa. This suggests that unselective grazers, which feed on a broader size spectrum from bacteria to small algae, may have a considerable competitive advantage in hypertrophic environments rich in small particles. Moreover, a meta‐analysis of available literature data supports our hypothesis that the role of ciliate bacterivory increases significantly, relative to HNF bacterivory, along a trophic gradient toward hypertrophic habitats.